2021
DOI: 10.7759/cureus.17067
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Nonunions and Delayed Unions Treated With Low-Intensity Pulsed Ultrasound Therapy: A Clinical Series

Abstract: The incidence of nonunion of fractures has been steadily rising owing to improved life expectancy following severe injuries along with rising cases of polytrauma. Once a nonunion is established, the chances of spontaneous healing are deemed to be quite low. Fracture nonunion continues to be a challenge in clinical practice with nonunions having a considerable impact on patient’s quality of life causing both functional and psychosocial disability. Low-Intensity Pulsed Ultrasound (LIPUS) therapy is being project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This included patients who were treated with initial surgical fixation (79% union) as well as patients who were managed conservatively (86% union). This is in keeping with the healing rates according to the data provided by Exogen as well as other recently published studies, whose success rates vary between 78% and 90% [10,[13][14][15]. An example of one of the successfully managed patients with LIPUS therapy can be appreciated in Figures 2-5.…”
Section: Discussionsupporting
confidence: 85%
“…This included patients who were treated with initial surgical fixation (79% union) as well as patients who were managed conservatively (86% union). This is in keeping with the healing rates according to the data provided by Exogen as well as other recently published studies, whose success rates vary between 78% and 90% [10,[13][14][15]. An example of one of the successfully managed patients with LIPUS therapy can be appreciated in Figures 2-5.…”
Section: Discussionsupporting
confidence: 85%
“…The overall healing rate of LIPUS for hypertrophic and atrophic bone discontinuity patients is 86.7 and 63.5% 30 . Though typically applied as an alternative to surgical treatment for nonunion and delayed healing, 38 LIPUS should be considered together with other treatments in situations of large fracture gaps and instability 30 . Tobacco affects bone metabolism, and smoking is a significant pathological component of fracture non‐union 39 .…”
Section: Lipus In Fracture Healingmentioning
confidence: 99%
“…LIPUS has also been used in clinical trials for fracture healing, and compelling clinical data demonstrate its effectiveness in bone fracture healing, especially in some high-risk non-union cases that are not suitable for surgery (Zura et al, 2015a;Rutten et al, 2016;Leighton et al, 2017;Bhan et al, 2021). Former studies have demonstrated that LIPUS is responsible for accelerating bone reparations through both upregulating osteogenic-specific genes and downregulating osteoclast differentiation (Costa et al, 2018;Meng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%